2023
DOI: 10.3390/agriculture13030730
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet Scattering Convolution Network-Based Detection Algorithm on Nondestructive Microcrack Electrical Signals of Eggs

Abstract: The detection of poultry egg microcracks based on electrical characteristic models is a new and effective method. However, due to the disorder, mutation, nonlinear, time discontinuity, and other factors of the current data, detection algorithms such as support-vector machines (SVM) and random forest (RF) under traditional statistical characteristics cannot identify subtle defects. The detection system voltage is set to 1500 V in the existing method, and higher voltages may cause damage to the hatched eggs; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Wavelet scattering transform is a method for analyzing multiple scales and frequencies, and can analyze signals through filler modulus, which can extract information and features about transform invariance [25,26]. In this way, it is possible to remove the characteristic information such as the period, frequency, and intensity of the heartbeat at various positions in the PCG signal, the noise of the measurement equipment generated during acquisition, and the noise generated in the surrounding environment.…”
Section: Wavelet Scattering Transformmentioning
confidence: 99%
“…Wavelet scattering transform is a method for analyzing multiple scales and frequencies, and can analyze signals through filler modulus, which can extract information and features about transform invariance [25,26]. In this way, it is possible to remove the characteristic information such as the period, frequency, and intensity of the heartbeat at various positions in the PCG signal, the noise of the measurement equipment generated during acquisition, and the noise generated in the surrounding environment.…”
Section: Wavelet Scattering Transformmentioning
confidence: 99%
“…The first category has eleven papers under the following sub-heading: Intelligent sensing for the crop or machine system [1,4,7,9,10,12,16,17,22,23,26]. Currently, a large number of studies focus on deep learning techniques, which have shown their superb impact on robotic sensing applications, as reflected in this issue.…”
mentioning
confidence: 99%
“…Currently, a large number of studies focus on deep learning techniques, which have shown their superb impact on robotic sensing applications, as reflected in this issue. Some papers utilized improved YOLO-based [7,23,26], CNN-based [12,16] or RCNN-based [9] methods to developed a detection model for operating target recognition or performance evaluation from the RGB images. To achieve more accuracy, faster and compacter models may be popular due to the cost-effective and feasiblity with low-computing platforms.…”
mentioning
confidence: 99%